Pulmonary artery endothelium resident endothelial colony-forming cells in pulmonary arterial hypertension - Duong, Heng T. (Medknow Publications & Media Pvt Ltd, 2011)
Proliferative pulmonary vascular remodeling is the pathologic hallmark of pulmonary arterial hypertension (PAH) that ultimately leads to right heart failure and death. Highly proliferative endothelial cells known as endothelial colony-forming cells (ECFC) participate in vascular homeostasis in health as well as in pathological angiogenic remodeling in disease. ECFC are distinguished by the capacity to clonally proliferate from a single cell. The presence of ECFC in the human pulmonary arteries and their role in PAH pathogenesis is largely unknown. In this study, we established a simple technique for isolating and growing ECFC from cultured pulmonary artery endothelial cells (PAEC) to test the hypothesis that ECFC reside in human pulmonary arteries and that the proliferative vasculopathy of PAH is related to greater numbers and/or more proliferative ECFC in the pulmonary vascular wall. Flow cytometric forward and side scatter properties and aggregate correction were utilized to sort unmanipulated, single PAEC to enumerate ECFC in primary PAEC cultures derived from PAH and healthy lungs. After 2 weeks, wells were assessed for ECFC formation. ECFC derived from PAH PAEC were more proliferative than control. A greater proportion of PAH ECFC formed colonies following subculturing, demonstrating the presence of more ECFC with high proliferative potential among PAH PAEC. Human androgen receptor assay showed clonality of progeny, confirming that proliferative colonies were single cell-derived. ECFC expressed CD31, von Willebrand factor, endothelial nitric oxide synthase, caveolin-1 and CD34, consistent with an endothelial cell phenotype. We established a simple flow cytometry method that allows ECFC quantification using unmanipulated cells. We conclude that ECFC reside among PAEC and that PAH PAEC contain ECFC that are more proliferative than ECFC in control cultures, which likely contributes to the proliferative angiopathic process in PAH.